(3GdfLe GdRGgQ aj JaSjQ GdeYLR GdHGgQs
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd Ydi YHOg GdcJGH ,hgjC dg GdCSHGH hCHGf Hg GdUhGH ,hNU CeJg HCaVd GdNWGH s
(3BNQgG (B:s
(3hbjd fRdJ ai EfJXGQ GdUdGg hgj GdQHGW s
(3HgG fXGe GdJYbjHIs
(3GdeDda gh CMO JdGePg YHO GdQMef Hf eMeO GddNeis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJaSjQ hYdhe GdbQBfs